1991
DOI: 10.1002/j.1552-4604.1991.tb03729.x
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Therapy in Hypercholesterolemia: Effect on Fibrinogen, Hemorrheologic Parameters, Platelet Activity, and Red Blood Cell Morphology

Abstract: The effect of lovastatin therapy on blood rheology was investigated in 26 hypercholesterolemic patients. Treatment with lovastatin was associated with a significant improvement in whole blood filtration time and a tendency toward normalization in red blood cell morphology. A significant increase was observed in fibrinogen level, in ADP-induced platelet aggregation, in the percentage of "big" platelets, and in platelet count. The viscosity of whole blood and plasma and the percentage of aggregated platelets did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 18 publications
2
28
0
1
Order By: Relevance
“…47,48 Because elevated fibrinogen levels represent a recognized risk factor for CAD and thrombosis and significantly affect plasma thrombogenicity, the effects of statins on fibrinogen concentrations have been studied extensively. It has been reported that these agents increase, 28,49 decrease, 34,50 or, in a majority of reports, have no effect on plasma fibrinogen levels. 24 -26,37-39,51, 52 Most, but not all, 34 of the studies, in which fibrinogen concentrations have been measured using the Clauss method, concluded that inhibition of HMG-CoA reductase did not affect fibrinogen concentrations.…”
Section: Fibrinogen and Fibrinmentioning
confidence: 96%
“…47,48 Because elevated fibrinogen levels represent a recognized risk factor for CAD and thrombosis and significantly affect plasma thrombogenicity, the effects of statins on fibrinogen concentrations have been studied extensively. It has been reported that these agents increase, 28,49 decrease, 34,50 or, in a majority of reports, have no effect on plasma fibrinogen levels. 24 -26,37-39,51, 52 Most, but not all, 34 of the studies, in which fibrinogen concentrations have been measured using the Clauss method, concluded that inhibition of HMG-CoA reductase did not affect fibrinogen concentrations.…”
Section: Fibrinogen and Fibrinmentioning
confidence: 96%
“…However, these studies have generally failed to provide consistent results. For example, lovastatin use has been associated with both an increase and decrease in fibrinogen levels [19,20]. Similar inconsistencies have been reported with the use of pravastatin, atorvastatin, and simvastatin [8โ€ขโ€ข,21].…”
Section: Thrombosismentioning
confidence: 62%
“…One study showed an increase in platelet sensitivity to ADP in patients treated with lovastatin for 26 weeks, despite a significant decrease in their LDL cholesterol levels. 12 In contrast, another study evaluated platelet aggregation in patients treated with lovastatin for 1 year and found a significant decrease in ADP-induced platelet aggregation. 14 We studied platelet function by using collagen and TRA in all 4 monkey groups.…”
Section: Discussionmentioning
confidence: 98%
“…9 Platelet aggregability has been shown to decrease with decreasing levels of LDL in patients with familial hyperlipidemia and in normolipidemic males. 10,11 HMG-CoA reductase inhibitors, such as lovastatin and pravastatin, lower LDL cholesterol, 12,13 which should result in decreased platelet sensitivity to aggregation. However, the actual effect of HMG-CoA reductase inhibitors on platelets is unclear.…”
Section: Discussionmentioning
confidence: 99%